Gender Participation in Cauliflower Seed Production at Sadar Upazila of Tangail District in Bangladesh - Haque, ME; Hasan, SS; Sarker, A (Journal of Agriculture & Rural Development, 2008)
The purpose of the study was to ascertain gender participation, particularly proportionate involvement of male and female in cauliflower seed production and also to identify the relationship between the selected characteristics of the farm households and their participation in cauliflower seed production in four intensive cauliflower seed producing villages of Sadar Upazila under Tangail District. A sample size of 70 respondents were interviewed by using an interview schedule. The study reveals that women played a significant role in cauliflower seed production along with their male counterparts. However, there were variations in participation in different activities performed for the production of cauliflower seed. A clear gender specific division of labor existed in farm families. Women were more involved in less laboring activities, such as gap filling, plant protection, scooping, drying and storage. While men were mostly involved in land preparation, manure and fertilizer collection and application, transportation in the field and weeding and mulching. A varied level of male-female joint involvement was observed. Involvement of women was minimum in land preparation while least involved in seed storage. Women's participation in different activities of cauliflower seed production increased with the decrease of family size, farm size, annual income and educational level of the family head of the farm households. Key words: Gender participation, cauliflower, seed production.